2015
DOI: 10.1186/s12936-015-1043-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antibody profiles in symptomatic malaria in three sentinel sites of Ivory Coast by using multiplex, fluorescent, magnetic, bead-based serological assay (MAGPIX™)

Abstract: BackgroundAdvances in malaria control have reduced the burden of disease resulting from exposure to parasite infections. The consequences on naturally acquired immunity are unclear. A magnetic bead-based immunoassay (MBA) to assess antibody levels in populations living in endemic areas was previously evaluated. In this study, the effect of clinical attacks on immunity was analysed in three sentinel sites of Ivory Coast.MethodsRecombinant proteins or peptides derived from liver or blood stage antigens of Plasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 49 publications
(73 reference statements)
2
53
0
1
Order By: Relevance
“…Helb et al [13] and Yman et al [12] estimated recent P. falciparum exposure at individual (longitudinal data) and population level (cross-sectional data). Studies based on longitudinal data mainly use approaches such as linear regression models [13, 20], generalized linear models (GLM) [64], or Ab-intensity models [12] to analyse Ab profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Helb et al [13] and Yman et al [12] estimated recent P. falciparum exposure at individual (longitudinal data) and population level (cross-sectional data). Studies based on longitudinal data mainly use approaches such as linear regression models [13, 20], generalized linear models (GLM) [64], or Ab-intensity models [12] to analyse Ab profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of patients from Côte d'Ivoire, parasite invasion strongly stimulates immune responses and antibody responses may be higher in more exposed persons who, therefore, have a higher degree of acquired immunity [37]. Cross-sectional analysis of randomly recruited symptomatic and well-documented cases from sentinel sites, showed that a multi-target measure of antibody responses could constitute a surrogate of actual immune status [25]. Here, IgG responses to SE, MSP1 and LSA1 41 in sentinel sites were compared with results from asymptomatic recruitment (AR) in Abobo and severe malaria cases (SM) from the CHU of Abidjan (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Individual informed written consent was obtained from participants/parents/guardians. All clinical cases were treated and followed-up according to the standard national procedure as described [25,26]. The study from Senegal was done in the endemic villages of Dielmo and Ndiop, where a long-term longitudinal survey designed to study acquisition and maintenance of natural immunity has been carried out over 20 years [4,6,30].…”
Section: Study Area and Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…21. Moreover, assays for evaluation of the serological antibody and/or cytokine/chemokine response to infections such as leptospirosis,22 rotavirus and flavivirus infections,23 24 malaria,25 toxoplasmosis26 and cryptosporidiosis27 have also been reported.…”
Section: Discussionmentioning
confidence: 99%